UJI ECOPRINT UNTUK TUMBUH KEMBANG WIRAUSAHA DI ERA PANDEMI COVID-19-KELURAHAN SEMBUNGHARJO GENUK - Hardiningsih, Pancawati; Srimindarti, Ceacilia; Yunianto, Askar; Anugerah Adhipratama, Agung (Universitas katolik Musi Charitas, 2022)
The economic contraction due to the Covid-19 pandemic has caused millions of people to lose their jobs, causing the number of poverty rates to increase. The existence of this situation encourages people to think of ways to earn income by utilizing plants, leaves in the surrounding environment as a form of ecoprint business. This batik model is very environmentally friendly and does not cause water, soil or air pollution. This ecoprint can grow new and independent entrepreneurs by being provided with facilities and skills from creativity and potential in accordance with regional capabilities. The training was carried out in stages, namely the process of handling fabrics with the ngetel (cooking) technique; fabric handling process with mordanting technique; and ecoprint engineering processes. The results of this service activity show that housewives are able to produce fabric products with ecoprint techniques, and produce one community, namely the genuk people's batik studio. Service evaluation is carried out by monitoring the activities of participants after the training and seeing the final results of the fabrics modified by participants according to the expertise of each participant through the formation of a WhatsApp(WA) group.